Bayesian Spatio Temporal Car Localized Model For Mapping The Relative Risk Of AIDS In South Sulawesi Province - Taufik, Andi Gagah Palarungi; Aswi, Aswi; Annas, Suwarni (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2025)
Acquired Immune Deficiency Syndrome (AIDS) remains a major public health issue in Indonesia, with South Sulawesi showing a marked rise in cases from 2022 to 2024. This study aims to estimate and visualize the relative risk of AIDS across 24 districts and municipalities in the province by incorporating population density as a spatial covariate. Data were obtained from the Central Bureau of Statistics (BPS) and the South Sulawesi Provincial Health Office. A Bayesian Localised Conditional Autoregressive (CAR) spatio-temporal framework was applied to account for both spatial dependence and temporal variation. Model selection was guided by the Deviance Information Criterion (DIC) and the Watanabe–Akaike Information Criterion (WAIC), with the best-fitting model identified at G = 3 using an Inverse-Gamma (1; 0.01) prior. The analysis revealed that population density had a significant positive association with AIDS incidence. Areas with higher density exhibited elevated relative risk values, particularly Makassar City (RR = 1.95) and Gowa Regency (RR = 1.82), whereas the lowest risks were found in Selayar (RR = 0.41) and East Luwu (RR = 0.45). These findings indicate distinct spatial clustering patterns and underscore the need for geographically focused intervention policies.